2020
DOI: 10.1002/eco.2260
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on migration patterns and pathways of a threatened potamodromous fish in a regulated lowland river network

Abstract: In riverine ecosystems, movements of biota among different parts of the river network are fundamental to the functioning and sustainability of populations, especially for fish. Globally, human activities (e.g., dam construction and altered flow regimes) have impaired riverine fish movements through reduced river connectivity, leading to well‐documented population declines. This study examined the timing and extent of movement of a nationally threatened potamodromous fish, silver perch (Bidyanus bidyanus), amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Several studies have documented movement of Murray River silver perch into other connected habitats (e.g. Zampatti et al 2018;Koster et al 2021). Further, Zampatti et al (2018) identified that some silver perch captured in the lower Murray River exhibited a Darling River natal origin.…”
Section: Life History and Movement Among Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have documented movement of Murray River silver perch into other connected habitats (e.g. Zampatti et al 2018;Koster et al 2021). Further, Zampatti et al (2018) identified that some silver perch captured in the lower Murray River exhibited a Darling River natal origin.…”
Section: Life History and Movement Among Speciesmentioning
confidence: 99%
“…Reynolds 1983;Llewellyn 2014;Thiem et al 2020). These large movements are often associated with periodic spawning in adult golden perch and silver perch, and the subsequent long-distance dispersal of eggs, larvae and juveniles (Koster et al 2021;Stuart and Sharpe 2020). By contrast, long-distance movements of adult Murray cod appear facultative and are not required for reproduction, with predictable annual spawning occurring under a range of river discharges and the well-developed larvae of this nesting species able to actively settle out in favourable, localised habitats (Reynolds 1983;Kopf et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, there is growing recognition of the potential importance of tributaries to the population dynamics of riverine fish in flow-regulated rivers (Rice et al 2008;Pracheil et al 2013;Koster et al 2021). Tributaries that preserve the hydrological and hydraulic conditions that promote spawning and recruitment may subsequently provide a source of recruits to flow-affected main channel habitats (Pollux et al 2006;Webber et al 2013).…”
Section: Natal Originmentioning
confidence: 99%
“…For golden and silver perch, migration of both adults and juveniles is an important life history strategy for reproduction and dispersal (e.g., Koster et al. 2020, Stuart and Sharpe 2020) with recruitment highly variable through space and time (Zampatti and Leigh 2013, Tonkin et al. 2019).…”
Section: Introductionmentioning
confidence: 99%